Discussions on the Russian World - E. Koldunova (Сравнительная политика, 2016)
Book Review: Kirill, Patriarch of Moscow and All Rus’. Seven Speeches on Russian World (in Russian) / Comp. by A.V. Shhipkov. Moscow: Vsemirnyj Russkij Narodnyj Sobor, 2015.